(untitled) (World Bulletin of Public Health, 2022)
Acute viral respiratory infections can increase the risk of progression of a pre-existing condition, including a cardiovascular pathology. Lifethreatening complications of Coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) necessitate research into the cardiovascular effects of COVID-19 crucial for developing adequate treatment strategy for infected patients, especially those of advanced age. This article reviews the literature on the clinical and functional characteristics of patients with COVID-19, including those with poor outcomes